2007
DOI: 10.1038/sj.gene.6364420
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression in lupus-associated IL-10 promoter single-nucleotide polymorphisms is mediated by poly(ADP-ribose) polymerase-1

Abstract: Systemic lupus erythematosus (SLE) is a complex, multifactorial autoimmune disease characterized by the dysregulation of T and B cells that leads to hyperactivity of B cells and production of autoantibodies, and involves both environmental and genetic factors. Interleukin-10 (IL-10) is a candidate susceptibility gene in SLE. In particular, three IL-10 promoter singlenucleotide polymorphisms (SNPs; À1082A/G, À819T/C and À592A/C) are strongly associated with the pathogenesis of SLE. We found that the homozygous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 72 publications
2
18
0
1
Order By: Relevance
“…Of note, the most consistently replicated genotype-by-dust mite allergen interaction (rs1800896-by-dust antigen level) in our study involves a well described functional variant in IL10. Although many studies have shown decreased IL-10 production associated with the common A allele compared with the G allele of rs1800896, 35,36 others have demonstrated the opposite effect, 23 and 1 study showed no effect. 37 On the basis of these previous studies and our current findings, we speculate that the effect of functional promoter polymorphisms in IL10 on IL-10 transcription by may be complex and linked to the degree of exposure to specific antigenic stimuli (as would be predicted in Fig 1).…”
Section: Discussionmentioning
confidence: 93%
“…Of note, the most consistently replicated genotype-by-dust mite allergen interaction (rs1800896-by-dust antigen level) in our study involves a well described functional variant in IL10. Although many studies have shown decreased IL-10 production associated with the common A allele compared with the G allele of rs1800896, 35,36 others have demonstrated the opposite effect, 23 and 1 study showed no effect. 37 On the basis of these previous studies and our current findings, we speculate that the effect of functional promoter polymorphisms in IL10 on IL-10 transcription by may be complex and linked to the degree of exposure to specific antigenic stimuli (as would be predicted in Fig 1).…”
Section: Discussionmentioning
confidence: 93%
“…125 Both factors are implicated in the expression of IL-10 in murine macrophages. 126 In response to apoptotic and perhaps necrotic cells, p38 signaling leads to PBX1 and PREP1 recruitment to a putative apoptotic cell response element (ACRE) in the IL10 promoter that is conserved between human and mouse (163 bp upstream of the translation start site). 126 In this context, IL-10 induction was correlated not with phagocytosis but instead scavenger function, implicating IL-10 in regulating tissue restoration and/or homeostasis.…”
Section: Transcriptional Regulation Of Interleukin 10mentioning
confidence: 99%
“…As an enzyme, PARP1 acts on chromatin remodeling complexes to control DNA accessibility for RNA polymerase [18,19,20,21,22]. PARP1 also functions as a transcription factor by binding an octamer motif in promoter elements to regulate gene expression [23,24,25,26,27,28,29,30]. Interestingly, despite the roles of PARP1 in DNA repair and transcription, little is known about how one process affects the other.…”
Section: Introductionmentioning
confidence: 99%